Achieving equiaxed and lamellar TiAl alloys via cold-cathode electron beam additive manufacturing with dual-wire synergistic control - Yilei Shi; Shuili Gong; Haiying Xu; Wei Chen; Zhuang Wang; Guang Yang; Xin Liu; Bojin Qi (Journal of Materials Research and Technology)
TiAl alloy, renowned for its high temperature resistance while maintaining lightweight properties, serves as a crucial structural material for hot-end components. However, the widespread application of additive manufacturing (AM) for TiAl alloys is constrained by their limited ductility. To enable the engineering-scale production of TiAl alloys with enhanced strength and ductility, this study introduces advancements in the heat source, material composition, and deposition processes. The characteristics of the cold-cathode electron beam heat source were used to manufacture low-cost in-situ alloyed TiAl alloys through wire-fed electron beam additive manufacturing. Mo, Zr, and Si elements were introduced into the TiAl alloy, and precise thermal control allowed the separated twin wires to simultaneously form a stable co-molten pool, and the specimens with good appearance and no internal microcracks and pores were obtained. Furthermore, a detailed comparison between Ti48Al alloy and Ti48Al1Mo0.45Zr0.3Si alloy was carried out, focusing on aspects such as grain morphology, chemical composition homogeneity, phase constitution, and mechanical properties. The influence of dual-wire synergistic control on process stability, microstructure evolution, and strengthening mechanisms was discussed. The results show that the cold-cathode electron beam heat source under low vacuum and the co-molten pool mode reduce aluminum evaporation and promote element mixing through layer-by-layer temperature control and remelting. Compared to the lamellar microstructure of Ti48Al alloy, the Ti48Al1Mo0.45Zr0.3Si alloy exhibits a dual-γ phase microstructure, consisting of fine lamellar colonies and equiaxed γ grains. This modification led to a 90% and 150% increase in elongation at room temperature and 650 °C, respectively. These findings offer important insights into enhancing the performance of TiAl alloys through cost-effective alloying strategies.